Quality of life prior and in the course of the COVID-19 pandemic : a nationwide cross-sectional study with Brazilian dietitians - Matos, Raquel Adjafre da Costa (2021)
This paper is an extended version of our conference paper published in Proceedings of the 3rd International Electronic Conference on Environmental Research and Public Health—Public Health Issues in the Context of the COVID-19 Pandemic: Online, 11–25 January 2021.